2007
DOI: 10.1631/jzus.2007.b0860
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis for brix weight per stool and its component traits in sugarcane (Saccharum officinarum)

Abstract: Brix weight per stool (BW) of sugarcane is a complex trait, which is the final product of a combination of many components. Diallel cross experiments were conducted during a period of two years for BW and its five component traits, including stalk diameter (SD), stalk length (SL), stalk number (SN), stalk weight (SW), and brix scale (BS) of sugarcane. Phenotypic data of all the six traits were analyzed by mixed linear model and their phenotype variances were portioned into additive (A), dominance (D), additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…According to Milligan et al (1990), a positive correlation between DS and Brix is to be expected because large stalk diameters tend to produce a high concentration of juice. In this study, the traits HS and DS showed moderate additive correlation, and other studies (Liu et al, 2007) have reported similar results. High correlations (>0.90) were obtained for WS with HS, CY, and SY.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to Milligan et al (1990), a positive correlation between DS and Brix is to be expected because large stalk diameters tend to produce a high concentration of juice. In this study, the traits HS and DS showed moderate additive correlation, and other studies (Liu et al, 2007) have reported similar results. High correlations (>0.90) were obtained for WS with HS, CY, and SY.…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al (2007) found a significant and high dominance component for WS and also a significant effect of the interaction between dominance and site; however, limited information has been reported in the literature about this component. For HS, DS, and WS, further insight through appropriate experiments is required to determine if the component d 2 (Eq.…”
Section: Discussionmentioning
confidence: 87%
“…Future varieties bred specifically for secondgeneration biofuels will be dissociated from highsucrose yields, but instead will aim at total biomass production per area.Some traits are additive while others present dominant effects. Additive effects can be useful for breeding in early generations of the program while dominant effects are more useful in hybrids (Liu et al, 2007). Increase of sugar yield has always been a major goal of breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Some traits are additive while others present dominant effects. Additive effects can be useful for breeding in early generations of the program while dominant effects are more useful in hybrids (Liu et al, 2007). Increase of sugar yield (tons of pol per hectare, TPH) has always been a major goal of breeding programs.…”
Section: Production Goalsmentioning
confidence: 99%